A structural viscosity model for silicate slag melts based on MD simulation. Issue 19 (1st October 2022) - Xuan, Weiwei; Guhl, Stefan; Zhang, Yongquan; Zhang, Jiansheng; Meyer, Bernd
Abstract: Slag viscosity is one of the most important parameters for silicate melts. Slag properties are intrinsically dependent on structure. Complementary to established empirical viscosity models, this paper presents a structure-based viscosity model considering individual structure effects of major components. Based on the degree of polymerization and bond energy, a structural parameter RS, which reflects the network stability of melts, is calculated using a molecular dynamics simulation and correlated with the viscosity. The model coefficients are developed according to the viscosities of 54 published samples. A comparison is made with two commonly used viscosity models, the Urbain model and the modified Urbain model. The results indicate that the new model offers better predictions. Furthermore, we used 13 experimental samples including blast slags and coal slags to verify the new model; the results show that the experimental and calculated values are in good agreement. This model also reveals that the network stability ( RS ) can be regarded as a direct structural parameter for quantitative correlations with slag properties.